GE_GERICHTE A/2143/2023 vom 27. Juni 2024 - GE Cour de justice (2024)
AUGMENTATION(EN GÉNÉRAL);PERMIS DE CONSTRUIRE;ZONE AGRICOLE;FORMALISME EXCESSIF | LAT.22; LAT.16a; LAT.37a; OAT.43; LAT.24c; OAT.42.al3; RCI.9.al2